Association of non-alcoholic fatty liver disease with chronic kidney disease in type 2 diabetes mellitus - Rajender, Akash; Bhargava, Rajat; Choudhary, Priyanka; N., Sheetal; Upadhyay, Shalini; Singh, Gopal; Nepalia, Subhash; Rijhwani, Puneet (International Journal of Research in Medical Sciences, 2019)
Background: Non-alcoholic fatty liver disease (NAFLD) is closely associated with metabolic syndrome. NAFLD is considered a disease of no consequence. Data on the effect of NAFLD on renal dysfunction in T2DM is sparse. Author aimed to study the association of NAFLD with CKD in Indian T2DM subjects. Methods: In an observational cross-sectional study at Mahatma Gandhi Medical College and Hospital, Jaipur, Rajasthan, India from February 2017 to March 2018. 197 out of 268 randomly selected type 2 diabetes mellitus (T2DM) subjects were selected for the study after considering the inclusion and exclusion criteria. CKD was defined as estimated GFR <60 ml/min per 1.73 m2 and/or albumin to creatinine ratio ≥30 mg/g. NAFLD was diagnosed using ultrasonography. The association between NAFLD and CKD was analyzed using SPSS (version 24.0). Results: On ultrasonography 133 (67.5%) T2DM subjects had NAFLD. Diabetic with NAFLD (133, 67.51%) had significantly more history of hypertension (p 0.006), higher systolic (p 0.03) and diastolic BP (p 0.009), higher BMI (p <0.001), waist circumference (p <0.001), fasting glucose (p 0.03), triglyceride (p<0.001) and higher urinary albumin-to-creatinine ratio (p <0.001). Diabetics with CKD (61, 30.96%), were older (p 0.03), hypertensive (p <0.001) and had higher fasting glucose (p 0.003). Subjects with CKD had a higher prevalence of underlying NAFLD (78.69% vs 62.5%, p 0.03) as compared with diabetics with no CKD. T2DM subjects with NAFLD had more than two times (OR 2.88 (1.1-6.78), p 0.03) the risk of developing CKD after multivariate analysis as compared to subjects without NAFLD. Conclusions: NAFLD is a risk factor for development of CKD in patients of type 2 diabetes mellitus. Screening and early preventive measures may go long way in reducing morbidity.